Barriers and Facilitators of Health Literacy among D/deaf Individuals: A Review Article - Tahereh NASERIBOORIABADI; Farahnaz SADOUGHI; Abbas SHEIKHTAHERI (Tehran University of Medical Sciences, 2017)
Background: The implication of health literacy is the ability of individuals to find, understand, and use their required health information from reliable sources. It is an indicator of the individuals' participation in their own medical decision-making. Deaf individuals have limited health literacy and poor health status due to low literacy. Hence, this review was conducted to understand barriers and facilitators influencing health literacy among deaf community. Methods: We searched the ISI Web of Sciences, Scopus, and Medline from 1987 to 2016. Seventy-three papers were analyzed thematically. Results: We found three primary themes, including inadequate health literacy, barriers, and facilitators to accessing health information and health care services among deaf individuals. Facilitators were composed of four sub-theme including legal activities protecting the right of deaf patients to accessing health services, training health professionals about effective communication with deaf patients, providing sign language interpreter services, and developing deaf-tailored educational health programs and materials. Conclusion: Closing the deaf cultural gap and their limited access to health information are achievable through the removal of the communication barriers, allowing deaf individuals with more access to health learning opportunities, and informing the hearing community about the communicative skills of deaf individuals.